Income Analysis Of Coffee Farmers In The Albizia Forest Area Based On Agroforestry - Anang Susanto; Indah Rekyani Puspitawati; Lucas William Mendes (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Coffee is one of the sufficient non-timber forest product commodities potentials. Indonesia is one of the largest coffee-producing countries in the world after Brasi. One of the uses of coffee is as a mixed drink that can be served at various banquets in a relaxed atmosphere. This study aims to determine people's income from coffee production in Kendal District, Ngawi Regency. The research was conducted from January to April 2020 with the research location located in Kendal District, Ngawi Regency, East Java Province. Research population These are all those in the Kendal District area. Technique Sampling in this study was the census method, namely 50 people who grow coffee. The research results show that acceptance obtained by respondents growing coffee in Kendal District Ngawi Regency IDR 763.080,000 per year, while expenses from coffee production of IDR. 61.150,000, - per year, so the income from coffee production of IDR. 701.930.000,-..